Perilaku Prososial pada Relawan Komunitas Peduli Kanker Anak dan Penyakit Kronis Lainnya (KPKAPK) Kota Palembang - Setiawan, Ari; Budiman, Budiman (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, Sumatra Selatan, 2021)
This study aims to determine the prosocial motivation of volunteers, to find out the obstacles faced by volunteers and to find out the reasons why volunteers can survive in KPKAPK. This research is a field research using case study method. Data collection techniques used semi-structured interviews, observation and documentation, and the subjects in this study were 3 volunteers and 4 year old informants. The results showed that the motivation of volunteers at first was not purely altruistic, but also based on seeking benefits for themselves, for those whose personal goals were achieved, many volunteers left the community. As for the volunteers who still survive because they begin to develop empathy to continue to do good, then they feel that the dimensions of self-functionality as volunteers are fulfilled. The dimensions of self-functionality include values, social, understanding, career, self- improvement and self-protection. Each subject has all six dimensions, but there is only one dimension that is the strongest as the reasons and goals for volunteers to survive. Constraints faced by volunteers consist of internal and external factors. Internal factors such as busyness, cost and boredom. External factors such as lack of support from the foundation, lack of facilities, too pressured by the foundation, lack of human resources, lack of synergy between volunteers and the lack of application of organizational sciences.